Effect of co-administered lopinavir/ritonavir and sulfamethoxazole/trimethoprim on kidney function and architecture of albino rats - Elias, Adikwu; Oputiri, Deo; Geoffrey, Oru-Bo Precious; Jimmy, Zidafamor; Rejoice, Obele; Marian, Asalagha; Ebibowei, Akpe; Anthony, Akpen; Ayaowei, Demien (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Human immunodeficiency virus/acquired immune deficiency syndrome is usually associated with co-infections which has allow the concurrent use of sulfamethoxazole/trimethoprim (SMX/TMP)+Lopinavir/ritonavir (LPV/r). The concurrent use of these drugs may have possible adverse effects on the kidney because they are individually associated with adverse renal events. This study, therefore evaluates the possible effect of co-administered SMX/TMP+LPV/r on kidney function and architecture of albino rats. Methods: Seventy five (75) animals which were divided into five groups were used in this study. Group A, which served as control, contained 15 animals which were treated with 1% ethanol orally. Group B-E, which contained 15 animals each, was further subdivided into three groups of five animals each. Animals in these groups were treated with oral doses of SMX/TMP (11.2/2.3 mg/kg), LPV/r (11.4/2.9 mg/kg), and combined doses of SMX/TMP+LPV/r for 2-8 weeks respectively. Serum levels of creatinine, urea, and uric acid were evaluated. Kidney tissue was evaluated for malondialdehyde (MDA), superoxide dismutase (SOD), and histopathological changes. Results: Treatment with single doses of SMX/TMP, and LPV/r, produced a time-dependent increase in serum creatinine and urea. But no significant synergistic effects on serum creatinine and urea were observed when these agents were co-administered. Treatment with single and combine doses of these agents had no significant effects on serum uric acid level. Treatment with single agents produced time-dependent increase in kidney MDA and decrease in SOD level but without any significant effects when these agents were co-administered. Kidney of animals treated with single doses of these agents showed hypercellarity of the interstitium of the glomeruli and vascular congestion with no synergistic effects when these agents were co-administered. Conclusion: Concurrent use of SMX/TMP+LPV/r in the management of HIV and co-infection may not have any deleterious effect on the renal system.